Cases, deaths and lethality due to COVID-19: analysis of social and assistance data from the Brazilian Northeast - Fernando José Guedes da Silva Júnior; Claudete Ferreira de Souza Monteiro; Altamira Pereira da Silva Reichert; Ana Patrícia Pereira Morais; José Maria Ximenes Guimarães; Evanira Rodrigues Maia; Talitha Rodrigues Ribeiro Fernandes Pessoa; Maísa Paulino Rodrigues (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2023)
Objective: To analyze the impact of the coverage of Primary Health Care, Human Development Index and Bolsa Família on the occurrence of cases, deaths and lethality due to COVID-19 in the Brazilian Northeast. Method: Descriptive, cross-sectional study, with data extracted from the state platforms for COVID-19, the Health Information System for Primary Care and the Institute for Applied Economic Research. Spearman and Kruskal-Wallis correlation tests were used. Results: It was found that 483,793 confirmed cases of COVID-19 and 19,307 deaths from this condition were reported in the Brazilian Northeast. Regarding the occurrence of COVID-19, the State of Ceará had the highest rate of cases (1200.83/100,000 inhabitants). It was observed that the greater the coverage of FHS, the greater the number of confirmed cases (r=0.855 and p-value=0.002) and deaths (r=0.818 and p-value=0.004) due to COVID-19. Conclusion: The Family Health Strategy is an organizational model of Primary Health Care powerful to cope with the pandemic, based on prevention, tracking among the most vulnerable groups, identification and notification of cases and deaths due to COVID-19.